Do Managerial Ownership, Gender Diversity, and Intellectual Capital Matter in Predicting State-Owned Companies Financial Distress? - Anna Kania Widiatami; Dhifah Amaliyah Fadli; Ida Nur Aeni; Ratieh Widhiastuti; Ahmad Nurkhin (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2023)
The downward movement of some Indonesian state-owned companies during the pandemic because of financial problems has resulted in more public scrutiny of the companies. Managers need to take extra caution to prevent the occurrence of financial distress. This study investigated the role of managerial ownership, gender diversity, and intellectual capital in predicting financial distress in state-owned companies. In doing so, three research hypotheses were formulated. Based on the purposive sampling method, 19 state-owned companies in the Indonesia Stock Exchange (IDX) were selected as the research sample. Secondary data from each company's annual report from 2017 to 2020 were documented, resulting in 76 firm-year data as the final sample. The panel data regression was applied to test the hypotheses. A robustness test was also carried out to check the result's consistency. The study reports that intellectual capital had a positive impact in predicting financial distress, while managerial ownership and gender diversity did not affect it. These results may provide insight for managers of state-owned companies to prevent financial distress earlier by increasing their intellectual capital.